2001
DOI: 10.4049/jimmunol.166.6.4185
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Generated by Heme Oxygenase-1 Suppresses the Rejection of Mouse-to-Rat Cardiac Transplants

Abstract: Mouse-to-rat cardiac transplants survive long term after transient complement depletion by cobra venom factor and T cell immunosuppression by cyclosporin A. Expression of heme oxygenase-1 (HO-1) by the graft vasculature is critical to achieve graft survival. In the present study, we asked whether this protective effect was attributable to the generation of one of the catabolic products of HO-1, carbon monoxide (CO). Our present data suggests that this is the case. Under the same immunosuppressive regimen that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
338
3
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(364 citation statements)
references
References 37 publications
15
338
3
6
Order By: Relevance
“…This inhibitory action of HO-1 is mediated by CO; however, it does not involve the cGMP signaling pathway since the administration of lipophilic analogues of cGMP or the inhibition of soluble guanylate cyclase has no effect on the expression of either of these mitogens. Similarly, studies in our laboratory and others found that HO-1-derived CO inhibits platelet aggregation, thereby preventing the release of growth factors from platelet alpha granules (Wagner et al, 1997;Sato et al, 2001). In this case, the anti-aggregatory effect of CO is mediated by cGMP since it is associated with a marked increase in platelet cGMP and is prevented by soluble guanylate cyclase inhibitors (Brune and Ullrich, 1987;Wagner et al, 1997).…”
Section: Ho-1 and Cell Proliferationmentioning
confidence: 73%
See 1 more Smart Citation
“…This inhibitory action of HO-1 is mediated by CO; however, it does not involve the cGMP signaling pathway since the administration of lipophilic analogues of cGMP or the inhibition of soluble guanylate cyclase has no effect on the expression of either of these mitogens. Similarly, studies in our laboratory and others found that HO-1-derived CO inhibits platelet aggregation, thereby preventing the release of growth factors from platelet alpha granules (Wagner et al, 1997;Sato et al, 2001). In this case, the anti-aggregatory effect of CO is mediated by cGMP since it is associated with a marked increase in platelet cGMP and is prevented by soluble guanylate cyclase inhibitors (Brune and Ullrich, 1987;Wagner et al, 1997).…”
Section: Ho-1 and Cell Proliferationmentioning
confidence: 73%
“…Inhalation of low doses of CO (10-500 ppm) has been shown to protect tissues against hyperoxia, transplant rejection, and ischemia-reperfusion (Otterbein et al, 1999;Fujita et al, 2001;Sato et al, 2001). Presently, comparable concentrations of inhaled CO are used diagnostically to estimate lung diffusing capacity in patients, raising the possibility that inhaled CO may be used therapeutically .…”
Section: Ho-1 As a Therapeutic Target In Vascular Diseasementioning
confidence: 99%
“…It is a complex process influenced by coagulation and fibrinolytic pathways [9,10], inflammation [11], and hypercholesterolemic state [12]. The first line of evidence supporting the anti-thrombotic effect of HO-1 in vivo is the observation that CO suppressed vascular thrombosis occurring during the cardiac graft rejection likely through inhibiting platelet aggregation [13]. Subsequently, there was a study showing that CO protected ischemic lung injury through down regulating the expression of plasminogen activator inhibitor-1 (PAI-1), the principal regulator of the fibrinolytic system, in macrophages and derepressing fibrinolysis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide, which is chemically very similar to nitrogen monoxide (NO) (11), can bind to the heme groups in various proteins to modulate their function. By this property, it has been shown that CO may initiate intracellular signaling cascades related to cell survival, mimicking the effects of HO-1 induction (2,5,12,13). Finally, when heme is provided to cells, the generation of Fe via the HO-1-catalyzed reaction induces ferritin (Ft; ubiquitous iron storage protein) synthesis (14), which Ferris et al (15) demonstrated to decrease reactive oxygen species within cells by sequestering catalytic iron.…”
mentioning
confidence: 98%